Do Impairments Predict Hand Dexterity After Distal Radius Fractures? A 6-Month Prospective Cohort Study. (July 2018) - Bobos, Pavlos; Lalone, Emily A.; Grewal, Ruby; MacDermid, Joy C.
Background: The relationship of routinely measured grip and motion measures may be related to hand dexterity. This has not yet been thoroughly examined following a distal radius fracture (DRF). The purpose of this study was to investigate if impairments in range of motion (ROM) and grip strength predict hand dexterity 6 months following a DRF.Methods: Patients with DRFs were recruited from a specialized hand clinic. Hand grip was assessed with a J-Tech dynamometer; ROM was measured using standard landmarks and a manual goniometer. Multiple regression analyses were performed to identify whether potential predictors (grip, ROM, age, hand dominance, and sex) were associated with 3-month or 6-month outcomes in large- and small-object subtests of the NK dexterity test in the affected hand.Results: Age, sex, and arc motion for radial-ulnar deviation were significant predictors of large-object hand dexterity explaining the 23% of the variation. For small-object hand dexterity, age and flexion-extension arc motion were significant predictors explaining 11% of the variation at 3 month after the fracture (n = 391). At 6 months post injury (n = 319), grip strength, arc motion for flexion-extension, and age were found to be significant predictors of large-object dexterity explaining 34% of the variance. For the small objects, age, grip strength, sex, and arc motion of radial-ulnar deviation explained 25% of the variation.Conclusions: Although this confirms that the impairments in ROM and grip that occur after a DRF can explain almost one-third of the variation in hand dexterity, it also suggests the need for dexterity testing to provide more accurate assessment.